Obstetrical and perinatal outcome in adolescent pregnancy: a retrospective study at a tertiary care center in rural India - Shruthi, Arpitha; S. R., Sheela; Kesani, Vishnu Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Adolescent pregnancy is a serious health and social problem worldwide. The aim of this study was to determine the obstetrical and perinatal outcomes of nulliparous adolescent pregnancies in a tertiary care centre in rural India. Methods: This is a retrospective study conducted between April 2017 and March 2018.Adolescent primigravidae completing 28 weeks of gestation with singleton pregnancy were included in the study group. Primigravidae aged between 20 and 25 years were taken as a control group. The factors under study included obstetric complications and neonatal outcomes. The association was considered significant at P-value <0.05. Results: 450 women were included in the study group and 460 to the control group. The incidence of adolescent pregnancy was 18.3% during the study period. The adolescent mothers had a significantly higher incidence of preeclampsia (12.8 % vs 8.4 %; p = 0.03), eclampsia (3.5% vs 1.5%; p = 0.01), preterm delivery (18.6% vs 10.8%; p = 0.0009), low birth weight (39.1 % vs 24.2 %; p = 0.00001),very low birth weight babies (13.7 % vs 8.7 %; p = 0.01) compared to control group. There was higher proportion of NICU admissions in adolescent group (20.8% vs 12.3 %; p = 0.0005) compared to control group. No significant difference was found regarding postpartum complications and still birth. Conclusions: Adolescent pregnancy is associated with poorer feto-maternal outcomes. Regular antenatal visits, adequate nutritional supplementation and early detection of high-risk factors may contribute in decreasing the obstetric risk of childbirth in adolescent mothers.